Unemployment anxiety of last year college students - Yasar, Onur Mutlu; Turgut, Murat (Birlesik Dunya Yenilik Arastirma ve Yayincilik Merkezi, 2020)
The negative effects of anxiety on people, such as lack of self-confidence, deterioration of sleep order and social relations skills, feeling of failure, have been stated in many scientific studies. Youth unemployment is very high in the World and Turkey. The aim of this study was to determine the anxiety levels of the last year university students in sports science education. The research was carried out using quantitative research method. A total of 226 students from the School of Physical Education and Sports (fourth grade) of Kastamonu University participated in the study. In the research, Unemployment Anxiety Scale consisting of 5 sub-dimensions and 21 items was used as a measurement tool. In addition, it was observed that there was no statistical difference between men and women, but according to the variable of education department, it was determined that students of the sports management department have higher levels of unemployment anxiety. Keywords: Anxiety, college, student, unemployment, job, future-anxiety.
Keywords: 4. Education; 8. Economic growth